2001
DOI: 10.1115/1.1383972
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Bulk Flow Pulsations on Phase-Averaged and Time-Averaged Film-Cooled Boundary Layer Flow Structure

Abstract: Flow structure in boundary layers film cooled from a single row of round, simple angle holes, and subject to bulk flow pulsations, is investigated, including phase-averaged streamwise velocity variations, and alterations of time-averaged flow structure. The bulk flow pulsations are in the form of sinusoidal variations of velocity and static pressure, and are similar to flow variations produced by potential flow interactions and passing shock waves near turbine surfaces in gas turbine engines. Injection hole le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 23 publications
2
5
0
Order By: Relevance
“…It has been reported that the film cooling efficiency generally decreases when there is pulsation in the bulk flow. In particular, it has been reported that the film cooling efficiency decreases by about half when the pulsation frequency and blowing ratio are 32 Hz and 0.5, respectively [12,15,26], as observed in this study as well. As illustrated in Figure 3, both LES and URANS reproduced the decrease in film cooling efficiency upon the application of pulsation, although the RANS realizable k-ε model overpredicted the centerline effectiveness.…”
Section: Mesh Sensitivity Testsupporting
confidence: 84%
See 3 more Smart Citations
“…It has been reported that the film cooling efficiency generally decreases when there is pulsation in the bulk flow. In particular, it has been reported that the film cooling efficiency decreases by about half when the pulsation frequency and blowing ratio are 32 Hz and 0.5, respectively [12,15,26], as observed in this study as well. As illustrated in Figure 3, both LES and URANS reproduced the decrease in film cooling efficiency upon the application of pulsation, although the RANS realizable k-ε model overpredicted the centerline effectiveness.…”
Section: Mesh Sensitivity Testsupporting
confidence: 84%
“…The streamwise velocity profile obtained using LES predicted this peak well, whereas the various RANS models failed to predict the peak exactly, as shown in Figure 10a. In Figure 10b, the time-averaged dimensionless streamwise velocity profiles at 32 Hz obtained by LES match well with the experimental results [15], whereas the RANS realizable k-ε model did not predict the velocity profile between y/D = 0 and 1 exactly, and the velocity gradient predicted by RANS was rather different from those in the experimental and LES results. Figure 11 shows the time-averaged dimensionless U rms profiles at x/D = 5 and z/D = 0 for 0 and 32 Hz.…”
Section: Q-criterion Contours At Z/d = 5 and Y/d =supporting
confidence: 61%
See 2 more Smart Citations
“…Although HWA is an intrusive measurement method, it is still widely preferred because the hot-wire anemometer is the only device capable of delivering a truly analog output at high frequencies. HWA is also an accurate method for low-velocity measurements [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%